Prevalence and factors associated with anxiety, depression and burnout in gynecology and obstetrics residents during the COVID-19 pandemic - Maria Luiza de Castro Amaral; Isabela Michel da Silva; Alexandre Ferreira Bello; Franciele Cascaes da Silva; Gustavo Salata Romão; Alberto Trapani Júnior (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To determine the prevalence of anxiety, depression and burnout in residents of Gynecology and Obstetrics during COVID-19 pandemic in Brazil and its associated factors. Methods: Cross-sectional study involving all regions of Brazil, through the application of a sociodemographic questionnaire, the Hospital Anxiety and Depression Scale (HAD) and the Maslach Burnout Inventory (MBI-HSS) instrument. Multivariate analysis was performed after adjusting the Poisson model. Results: Among the 719 participating medical residents, screening was positive for anxiety in 75.7% and for depression in 49.8% of cases. Burnout syndrome was evidenced in 41.3% of the physicians studied. Those with depression are more likely to have anxiety (OR 0.797; 95%CI 0.687 - 0.925) and burnout syndrome (OR 0.847 95%CI 0.74 - 0.97). Residents with anxiety (OR 0.805; 95%CI 0.699 - 0.928) and burnout (OR 0.841; 95%CI 0.734 - 0.963) are more likely to have depression. Conclusion: High prevalence of anxiety, depression and burnout were found in residents of Gynecology and Obstetrics in Brazil, in addition to important correlations between anxiety-depression and depression-burnout.